Effectiveness of Self Instructional Module (Sim) on Knowledge Regarding Alzheimer's Disease - Neupane, Nira; Vijaya lakshmi, M. (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Alzheimer's disease is a progressive neurodegenerative disease that causes severe deterioration of functional and cognitive abilities. As the leading cause of dementia in adults, it affects one in every 10 people who are more than 65 years of age. There is a vital need for student nurses with knowledge of Alzheimer's disease to provide high quality care for the growing number of patients. The use of effective nursing interventions for the management of Alzheimer's disease can help student nurses promote independence and quality of life for Alzheimer's disease patients. Thus this study is under taken to assess the effectiveness of the self instructional module (SIM) on nursing management of client with Alzheimer's disease among 4th year B. Sc. (N) students. MATERIALS AND METHODS: A quantitative evaluative research approach with pre experimental one group pre test and post test research design & non probability purposive sampling technique was used to select the 60 samples of B.Sc. (N) 4th year students. Self administered structured knowledge questionnaire were used to collect the information from the study samples. The prepared tool was validated by the experts and the reliability was established. The study was conducted in R.V. College of Nursing and Vidyakirana Institute of Nursing Sciences, Bangalore. The data was analyzed by descriptive and inferential statistics using SPSS version 19. RESULTS: Findings of the study shown that, the overall mean percentage pre test level of knowledge of B.Sc. Nursing 4th year studentswas 62.08%, and the pre test knowledge score was 35(58.33%) respondents were having moderately adequate knowledge, 13(21.67%) had inadequate knowledge and 12(20%) were having adequate knowledge regarding nursing management of clients with Alzheimer's disease. In the post test overall mean percentage post test level of knowledge was 84.37%. The post test knowledge score was 54(90%) respondents were having adequate knowledge and 06(10%) had moderately adequate knowledge after the administration of SIM. The overall obtained ''t'' value of knowledge 15.6 is highly significant at P< 0.01 level. The obtained chi-square value showed significant association between the pre test level of knowledge and certain socio demographical variables; gender (χ2 =5.12, df =1, p<0.05) and sources of information (χ2 =4.82, df=1, p<0.05). However, it did not show any significant association with other demographic variables of 4th Year B. Sc. (N) students. CONCLUSION: Findings of the study showed that majority of the student nurses were moderately adequate knowledge before administering the SIM. The SIM facilitated them to gain more knowledge regarding nursing management of client's with Alzheimer's disease which was evident in post test knowledge scores. Hence SIM was an effective strategy for providing information and to improve knowledge of students' nurses. Journal of Universal College of Medical Sciences (2016) Vol.04 No.02 Issue 14, page: 25-29